Indonesia : Technical Assistance Report-Report on Sectoral Financial Accounts and Balance Sheets Technical Assistance Mission. (IMF Staff Country Reports; Country Report, 2018)
As part of the Switzerland State Secretariat for Economic Affairs (SECO) project, a technical assistance mission visited Jakarta, Indonesia, during January 8-12, 2018, to develop the capacity to compile integrated sectoral accounts and balance sheets data. The mission reviewed the results of the work undertaken to implement the recommendations of the September 2017 mission.